GLOBALIZATION AND ITS IMPACT ON THE EUROPEAN HIGHER EDUCATION - Gvelesiani, Irina; Tvaltvadze, Darejan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The process of globalization acquires the greatest importance in today’s world. The ongoing technological changes, the rise of the knowledge economy and the growth of skill requirements in the labor market have influenced the changes in the landscape of education throughout the world. The emergence of Bologna Process has facilitated the creation of the European Higher Education Area, which can be assumed as a sample of uniformity of the European system of higher education. The Bologna Process is focused on the following strategies: modernization of higher education; connection and creation of national, regional and global educational spaces; enhancement of the attractiveness and competitiveness of the EHEA. The implementation of these strategies implies innovative processes, which build an awareness of traditions and raise a world-wide importance and attractiveness of the Bologna process.